Trends in Antimicrobial Consumption in Tertiary Care Hospitals in Costa Rica from 2017 to 2021: A Comparative Analysis of Defined Daily Doses per 100 Bed Days and per 100 Discharges - Cristina Fernández-Barrantes; Allan Ramos-Esquivel; Luis Esteban Hernández-Soto; Manuel Ramírez-Cardoce; Luis David Garro-Zamora; Jose Castro Cordero; Santiago Grau (MDPI AG, 2024)
Background: Antimicrobial consumption (AMC) data in Latin America are scarce and usually spread out across different sources used to make AMC calculations, making it difficult to both standardize and compare regions through similar time frames. The main objective was to analyze AMC trends in Social Security tertiary care hospitals in Costa Rica in the period spanning January 2017 to December 2021, using both the defined daily dose (DDD)/100 bed days and DDD/100 discharges. Methods: This is a retrospective observational study of antimicrobial consumption. Global consumption trends were calculated and expressed as DDD/100 bed days and DDD/100 discharges. Trends in antimicrobial consumption were analyzed using a simple linear regression model to determine potential differences in antimicrobial usage throughout the study's duration. Results: A statistically significant increase in the consumption expressed in DDD/100 discharges was observed in the following groups: carbapenems, 7.6% (trend: 64.68, p < 0.0001), trimethoprim-sulfamethoxazole: 12.6% (trend: 16.45, p < 0.0001), quinolones 9.4% (trend: 36.80, p = 0.02), vancomycin 2.0% (trend: 16.30, p = 0.03), echinocandins: 6.0% (trend: 15.17, p = 0.01) and azole antifungals: 12.10% (trend: 102.05, p < 0.0001). Additionally, a statistically significant increase of 10.30% in the consumption of azole antifungals expressed in DDD/100 bed days was observed (p = 0.0008). In contrast, a statistically significant decrease in consumption, expressed in DDD/100 discharges, was identified for cephalosporins −6.0% (p < 0.0001) and macrolides −16.5% (p < 0.0001). Macrolides also showed a downward trend in consumption, as expressed in DDD/100 bed days (−14.3%, p < 0.0001). According to World Health Organization (WHO) access, watch and reserve (AWaRe) classification trend analysis, only the reserve group showed a statistically significant upward change of 9.2% (p = 0.016). Conclusions: This five-year analysis demonstrated trends over time in overall antimicrobial consumption measured in DDD/100 bed days and DDD/100 discharge rates that correlate. In general, for all antimicrobials, after the implementation of antimicrobial stewardship programs (ASP), a downward trend is reported; in contrast, during the COVID-19 pandemic the AMC shows a general upward trend. The comparison between DDD/100 bed days and DDD/100 discharges allows for complementary comparisons to be made regarding antimicrobial exposure in a clinical setting.